Interacting Effect of Social Media Crisis Communication and Organizational Citizenship Behavior on Employees’ Resistance to Change During the COVID-19 Crisis: Evidence From University Employees in the Philippines - Puyod, Jenette Villegas (Animo Repository, 2021)
This research analyzes the effect of social media crisis communication on resistance to change of university employees in the Philippines during the COVID-19 situation. The study also consider the role of organizational citizenship behavior (OCB), which is hypothesized as a predictor of employees’ resistance to change, as well as a moderator that strengthens the effect of social media crisis communication on employees’ resistance to change. Survey data were collected from 522 employees from three public universities in the Philippines. The hypotheses are tested using partial least squares structural equation modeling. The results show that social media crisis communication and OCB are negatively related to employees’ resistance to change. Moreover, the moderating effect analysis indicated that OCB significantly intensified the negative effect of social media crisis communication on the employees’ resistance to change. This result implies that social media crisis communication can have a stronger impact on lowering employees’ resistance to change when OCB is highly expressed among employees.